The Effectiveness of the Problem-Based Learning Model Assisted by the PhET Simulation in Improving Students’ Learning Outcomes - Qothrunnada Qothrunnada; Hardiyanti Pratiwi; Atika Suryani; Fitri Rochana (Indonesian Journal of Educational Innovation, 2025)
Improving students’ physics learning outcomes remains a challenge, especially with static fluid materials, which are abstract and difficult to visualize. The purpose of this research is to investigate the impact of integrating the Problem-Based Learning (PBL) approach with PhET simulations on students’ achievement in learning static fluid concepts. The research employed a quasi-experimental method using a one-group pretest-posttest design, involving 30 students from class XI science. A multiple-choice test was utilized as the research instrument and analyzed through the N-gain formula to assess learning improvement. The findings revealed an increase in the average score from 52 in the pretest to 81.5 in the posttest, yielding an N-gain value of 0.51, which falls into the moderate category. Implementing the Problem-Based Learning (PBL) model supported by PhET Simulations proved effective in helping students visualize abstract concepts, enhancing their engagement during the learning process, and deepening their understanding of static fluid topics. These results suggest that combining problem-based learning approaches with interactive simulation tools can serve as an innovative method to enhance physics learning outcomes, particularly in conceptually challenging topics.